Edukasi dan Budidaya Umbi Yakon sebagai Upaya Pemberdayaan Masyarakat dalam Pengendalian Diabetes Melitus - Arita Murwani; Dwi Widiyaningsih; Yuli Nurullaili Efendi (Penerbit Widina, Widina Media Utama, 2025)
Background: The increase in the number of DM (Diabetes Miletus) in Wonosobo Regency, Central Java, especially in the highland areas, the largest of which is in Kejajar District, namely Buntu Village, with a percentage increase of 43% from 2000 to 2025, unfortunately, it was recorded that 50% of DM patients in this area (17 out of 34 patients) did not undergo medical treatment or management (diet), on the other hand, the Buntu Kejajar Wonosobo village grows abundantly with Yakon plants, but even though the majority of the community are farmers, they are unable to cultivate them because of the expensive price of seeds and the lack of knowledge in the cultivation and processing process, even though if this plant is used as an alternative treatment, especially for DM, it will certainly be very helpful for the community. The purpose of PMP is to increase public knowledge about DM and the benefits of the Yakon plant as an anti-diabetic food. The method is carried out through health education about DM, training in yakon tuber processing and the technology application stage with assistance in planting yakon using the tuber method with organic fertilizer, assistance and evaluation of activities are also carried out using post-tests and online monitoring for the sustainability of the program with the commercialization of yakon as a DM medicine and the expansion of yakon cultivation to improve the community's economy. The results of this PMP include planting 100 cultivated yakon trees, increasing the knowledge of 60% of cadres (PUS) about yakon processing and its benefits for diabetes, increasing the knowledge of the elderly about DM by 25%, increasing the knowledge of cadres and youth organizations about diabetic seams.ABSTRAKLatar belakang: Peningkatan angka penyakit DM (Diabetes Miletus) di Kabupaten Wonosobo Jawa Tengah khususnya kawasan dataran tinggi yang terbanyak berada di kecamatan kejajar yaitu Desa Buntu, dengan prosentase peningkatan 43% dari tahun 2000 hingga 2025, sayangnya tercatat pasien DM di wilayah ini 50% (17 dari 34 pasien) tidak melakukan pengobatan maupun tatalaksana secara medis (diet), disisi lain desa buntu kejajar Wonosobo tumbuh dengan subur tanaman Yakon namun meskipun masyarakat mayoritas petani mereka tidak mampu melakukan budidaya karena harga bibit yang mahal serta kurangnya pengetahuan dalam proses budidaya dan pengolahannya, padahal jika tanaman ini dijadikan alternatif pengobatan terutama untuk penyakit DM tentu akan sangat membantu masyarakat. Tujuan PMP Meningkatkan pengetahuan masyarakat tentang DM dan manfaat tanaman yakon sebagai salah satu makanan anti diabetik Metode dilakukan melalui edukasi kesehatan tentang DM , pelatihan pengolahan umbi yakon dan tahap penerapan teknologi dengan pendampingan penanaman yakon metode bonggol dengan pupuk organic, dilakukan juga pendampingan dan evaluasi kegiatan menggunakan post-test dan monitoring secara daring demi keberlanjutan Program dengan komersialisasi yakon sebagai obat DM dan perluasan budidaya yakon untuk meningkatkan perekonomian masyarakat Hasil PMP ini diantaranya Tertanamlah 100 pohon yakon yang dibudidayakan, meningkatnya pengetahuan sejumlah 60% Kader (PUS) tentang pengolahan yakon dan manfaatnya untuk diabetes, Meningkatnya Pengetahuan lansia tentang DM sebesar 25%, meningkatnya pengetahuan Kader dan karang taruna tentang seam diabetic.